Giving credit where credit is due: orbitofrontal cortex and valuation in an uncertain world. - Walton, M; Behrens, T; Noonan, M; Rushworth, M (2011)
The orbitofrontal cortex (OFC) has long been implicated in aspects of learning and adaptive decision making in changeable environments, but its precise role has remained elusive. One potential reason is that anatomical and functional distinctions within the OFC have often been overlooked. Here, we review findings centered largely on recent lesion studies in macaque monkeys from our laboratories that have investigated the causal role of the lateral and medial parts of the OFC (LOFC and MOFC) in choice behavior in uncertain, multioption environments. MOFC appears necessary for focusing attention on only the relevant decision variables to achieve a goal. By contrast, LOFC is required to allow rapid learning in changeable environments by enabling the credit for a particular outcome to be assigned to a specific choice.